TEKNIK TERAPI REALITAS DALAM MENINGKATKAN CITRA DIRI NEGATIF DILIHAT DARI RENDAHNYA KONSEP DIRI SISWA - Suci Nur Pratiwi; Siti Fatimah; Alvian Agung Nurhaqy (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2021)
This study aims to describe the negative self-image caused by the low self-concept in students of SMAN 1, Lareh Sago Halaban District, Lima Puluh Kota District. This research uses the literature review method. The results show that a person's self image can become unbalanced and distorted or unhealthy for many reasons. The lack of students' academic skills and abilities makes them insecure so that they display a negative self-image from an indication of their low self-concept. Therefore the solution for this is to provide guidance and counseling services by BK teachers who work in school. From this phenomenon and various solutions applied by several studies, the most appropriate and effective solution is to provide reality therapy counseling services with the aim of paying attention on the behavior of the counselee. A succesfull personality is achieved by te desire of the individual himself to change it, of course not forgetting self awareness and responsibility.  Keywords: Body- Image, Self-Concept, Reality Therapy Counseling